Rigid bronchoscopy in parturient: A balancing act - Mamta Dubey; Amit K Mittal; Nitesh Goel; Jitendra Dubey (Wolters Kluwer Medknow Publications, 2017)
We report a case of bronchial tumour excision in a pregnant female using a combination of rigid and flexible bronchoscope under general anaesthesia. This case report highlights the anaesthetic considerations regarding airway management of the parturient during rigid bronchoscopy and measures for preservation of utero-placental perfusion. Foetal heart rate monitoring using portable ultrasonography as a point-of-care device has been emphasised.